Analogous feature of cemento-ossifying fibroma and bone pathology: a clinico-pathological correlation (Journal of Pathology of Nepal, 2020)
Intra-osseous pathology of the craniofacial region is microscopically characterized by hypercellular fibroblastic stroma with a variable amount of bone or cementum like calcified structures. The overlapping histopathological features are not limited to lesions under one classification of similar origin rather it imbricates the lesions of entirely different origin as well.  The only possible way out then becomes the clinicopathological correlation. Hence, in an out of entire clinical, a radiographic, surgical, and histopathological feature reframes the building block for confirmatory diagnosis of a bone lesion.